2003
DOI: 10.1161/01.cir.0000074206.52056.2d
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Ablation of Paroxysmal Atrial Fibrillation Initiated by Non–Pulmonary Vein Ectopy

Abstract: Background-Most of the ectopic beats initiating paroxysmal atrial fibrillation (PAF) originate from the pulmonary vein (PV). However, only limited data are available on PAF originating from the non-PV areas. Methods and Results-Two hundred forty patients with a total of 358 ectopic foci initiating PAF were included.Sixty-eight (28%) patients had AF initiated by ectopic beats (73 foci, 20%) from the non-PV areas, including the left atrial posterior free wall (28, 38.3%), superior vena cava (27, 37.0%), crista t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
307
2
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 654 publications
(337 citation statements)
references
References 38 publications
6
307
2
4
Order By: Relevance
“…20,21,30,31 Among these common sites of non-PV triggers, the SVC accounted for 76% (28/37) of cases in our study, which was much higher than the range of 6% to 12% reported previously. 22,24,26 The higher incidence of SVC trigger observed in our study might be related to ethnic differences from previous non-Asian studies or our use of a broad definition of non-PV trigger.…”
Section: Prevalence Of Non-pv Triggerscontrasting
confidence: 72%
See 2 more Smart Citations
“…20,21,30,31 Among these common sites of non-PV triggers, the SVC accounted for 76% (28/37) of cases in our study, which was much higher than the range of 6% to 12% reported previously. 22,24,26 The higher incidence of SVC trigger observed in our study might be related to ethnic differences from previous non-Asian studies or our use of a broad definition of non-PV trigger.…”
Section: Prevalence Of Non-pv Triggerscontrasting
confidence: 72%
“…16,[19][20][21][22][23][24][25][26][27][28] Noninducibility of AF achieved by additional ablation after PVI is associated with lower AF recurrence compared with PVI alone. 23,24,28 However, Leong-Sit 29 et al reported that noninducibility of any atrial tachyarrhythmia is not predictive of clinical recurrence at a 1-year follow-up.…”
Section: Need For An Additional Procedural End Point Beyond Pvimentioning
confidence: 99%
See 1 more Smart Citation
“…Isoproterenol (5–20 μg/min) was injected intravenously before the procedure was completed. If sustained or nonsustained AF was reproducibly induced from non‐PV foci, they were focally ablated 16. When non‐PV foci were located in the superior vena cava, the superior vena cava was electrically isolated 17.…”
Section: Methodsmentioning
confidence: 99%
“…The concept that the onset and maintenance of AF require both a trigger and a substrate was well accepted. Ectopic foci occurring in muscular sleeves of PV or vena caval junctions were considered as critical AF triggers (Haïssaguerre et al, 1998;Lin et al, 2003). Selfperpetuation process of AF including structural (atrial fibrosis, dilation, etc.)…”
Section: Incidence Of Af Before and After Cpvimentioning
confidence: 99%